1998
DOI: 10.1002/(sici)1097-4652(199802)174:2<240::aid-jcp11>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of insulin-like growth factor binding proteins in human hepatic stellate cells

Abstract: Cultured hepatic stellate cells (HSCs), the cell type primarily involved in the progression of liver fibrosis, secrete insulin-like growth factor-I (IGF-I) and IGF binding protein (IGFBP) activity. IGF-I exerts a mitogenic effect on HSCs, thus potentially contributing to the fibrogenic process in an autocrine fashion. However, IGF-I action is modulated by the presence of specific IGFBPs that may inhibit and/or enhance its biologic effects. Therefore, we examined IGFBP-1 through IGFBP-6 mRNA and protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
(6 reference statements)
3
13
0
Order By: Relevance
“…This decrease is consistent with findings from previous binding protein studies in other tissues. 30,35 The changes in mRNA expression for IGFBP-5 and -6 may be correlated with decreased tissue levels of IGF-I; however, the changes occurred simultaneously rather than sequentially, suggesting the involvement of other cytokines. Addition of TGF-b1 to the culture medium decreased IGFBP-5 mRNA and protein expression in human hepatic stellate cells and IGFBP-6 expression in rat osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This decrease is consistent with findings from previous binding protein studies in other tissues. 30,35 The changes in mRNA expression for IGFBP-5 and -6 may be correlated with decreased tissue levels of IGF-I; however, the changes occurred simultaneously rather than sequentially, suggesting the involvement of other cytokines. Addition of TGF-b1 to the culture medium decreased IGFBP-5 mRNA and protein expression in human hepatic stellate cells and IGFBP-6 expression in rat osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
“…[23][24][25][26][27][28] These patterns vary according to individual tissue types and species. 29,30 Previous studies report that binding protein expression is upregulated in the synovial fluid of patients with rheumatoid arthritis and in osteoarthritic articular cartilage explants. 26,[31][32][33] From these reports, it is not unreasonable to assume that binding protein expression might also be upregulated in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] In most cases, however, enhanced DNA synthesis as measured by BrdU or 3 H-thymidine incorporation was taken to postulate the mitogenic effect of IGF-I. On the contrary, our data show that IGF-I Figure 4 Influence of IGF-I R and ERK1/2 receptor blockage on apoptosis of HSC (day 7) and rMF.…”
Section: Discussionsupporting
confidence: 69%
“…A similar expression pattern of these IGFBPs has been reported for rat HSC (30). In activated human HSC, Gentilini et al (31) detected expression of IGFBP-1 through -6 using an RNase protection assay. These authors also reported excretion of IGFBP-2 through -6 to be differentially regulated by IGF-1 and TGF-␤.…”
Section: Discussionmentioning
confidence: 99%